2021
DOI: 10.3390/ma14030650
|View full text |Cite
|
Sign up to set email alerts
|

Color and Translucency Stability of Three-Dimensional Printable Dental Materials for Crown and Bridge Restorations

Abstract: The purpose of this study was to examine and compare color and translucency stability of three-dimensional (3D) printable dental materials for crown and bridge restorations. Five different materials were investigated, and twelve disc-shaped specimens of two different thicknesses (1 and 2 mm) were prepared using a digital light processing 3D printer. Color measurements were made according to the CIELAB color scale (L*, a*, and b*) using a spectrophotometer 1 h, 1 day, 1 week, one month, and six months after pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 48 publications
(55 reference statements)
1
37
0
Order By: Relevance
“…In accordance with previous studies on temporary printed restorative materials [ 8 , 9 , 29 ], the results of the current in vitro experiment revealed that the tested 3D-printed material exhibited higher stain susceptibility compared to the milled material ( p < 001). Higher stain susceptibility of 3D-printed material may be attributed to the manufacturing technique, which results in multiple layers one stacked on top of the other.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In accordance with previous studies on temporary printed restorative materials [ 8 , 9 , 29 ], the results of the current in vitro experiment revealed that the tested 3D-printed material exhibited higher stain susceptibility compared to the milled material ( p < 001). Higher stain susceptibility of 3D-printed material may be attributed to the manufacturing technique, which results in multiple layers one stacked on top of the other.…”
Section: Discussionsupporting
confidence: 91%
“…Acknowledging the fact that the color measurement is influenced by the surrounding conditions as well as the geometry and thickness of the tested specimens, the design of a labial veneer restoration was selected for this study to best simulate clinical conditions compared to standard disc-shaped specimens commonly used in other color detection studies [ 8 , 9 , 14 , 19 , 22 , 23 , 24 ]. Furthermore, when the 3D-printing technique is used to fabricate anterior restorations, stair-stepping phenomena is anticipated, especially with the characteristic curved contour of such restorations [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shin et al [37] observed that water storage for a month resulted in water sorption, which could affect the optical properties of 3D-printed resins. Kim et al [38] conducted a study that assessed the translucency and color stability of 3D-printed provisional resins; they found minor changes in translucency and noted that 3D-printed dental prostheses had a yellowish color while their opacity increased after water storage for 6 months [38].…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) printing technique can manufacture the 3D physical consistent with the corresponding mathematical mode by stacking materials layer by layer [25][26][27]. Benefiting from its process flexibility and large-scale scalability, the cost-effective direct ink writing (DIW) method, known as 3D printing based on ink extrusion, opens the way for the next-generation power sources [28].…”
Section: Introductionmentioning
confidence: 99%